Fungal biofilms: Formation, resistance and pathogenicity - De Cássia Orlandi Sardi, Janaina [UNESP]; De Souza Pitangui, Nayla [UNESP]; Gullo, Fernanda Patrícia [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Mendes-Giannini, Maria Jose Soares [UNESP] (Taylor & Francis, 2015)
Biofilm formation has been detected quite early in the fossil record (~3.25 billion years ago) and is common throughout a diverse range of organisms in both the Archaea and bacteria lineages, including the ‘living fossils’ in the most deeply divided branches of the phylogenetic tree. The first report of microbial biofilms occurred in the 16th century, when Antonie van Leeuwenhoek noted the presence of “animalcules” on the plaque of his own teeth, but little was known about these microorganisms or how they came to be on his teeth. Bacterial aggregates had also been described by Pasteur in 1864 and by Henrici in 1933 in two independent observations, including one from rocks from an alpine stream (Geesy et al. 1977), which initiated the modern era of biofilms. The concept of biofilms appears with the observations of Jendresen’s dental biofilm and with a description of 77 masses of cells of Pseudomonas aeruginosa in the sputum and lung tissue of patients with chronic cystic fibrosis Høiby (Høiby et al. 1977). The term biofilm was introduced into medicine in 1985 by Nickel (Nickel et al. 1985).